A 'Property‐Owning Democracy' or 'Generation Rent'?. Issue 1 (14th February 2013) - Lund, Brian
Abstract: 'A property owning democracy' has been at the centre of Conservative Party social policy since Noel Skelton coined the phrase in 1924. The idea has been underpinned by contrasting the independent, hygienic, suburban homeowner with the urban, managed, flat‐dwelling, high‐density council tenant. No Conservative‐led government has left office with a homeownership rate lower than when it came to power and the right to buy has enabled this growth to be maintained. However, in 2005, homeownership started to decline and this drop has continued into the Coalition government's term of office with more households now exiting owner‐occupation into the private landlord sector than entering owner‐occupation from private renting. The 'reinvigorating' the right to buy is an attempt put a 'property owning democracy' back on track but, should it fail, the Conservative Party may turn to more radical policies such as sale on vacant possession of 'high value' local authority and housing association houses.